Removal of Decontaminating Agent from Aqueous Solution Using Microporous and Mesoporous Materials: Activated Carbon as an Effective Adsorbent - Narasimhan Gokulakrishnan; Arumugam Pandurangan; Pradeep Kumar Sinha (Adsorption Science & Technology)
Wastewater from nuclear plants contains oxalic acid, a chelating compound used to remove surface activity. This forms complexes with radioactive cations, thereby impeding their removal by conventional techniques. In this study, oxalic acid was removed by adsorption techniques using commercial activated carbon and various synthesised mesoporous materials, viz. Al-MCM-41 (Si/Al = 50), Al-MCM-41 (Si/Al = 100) and Si-MCM-41, as adsorbents, all of which were characterised by XRD, N 2 sorption and TEM analysis. The extent of oxalic acid removal was increased by optimising parameters such as the adsorbent employed, the contact time, the initial concentration of oxalic acid, the pH value of the aqueous solution and the temperature. Activated carbon removed a higher percentage of oxalic acid than any of the other adsorbents studied. The experimental data obtained could be fitted by the Langmuir adsorption model and also followed first-order kinetics. In addition, the negative value of the enthalpy obtained indicated that the adsorption process was exothermic in nature.